SYNTESIS AND INVESTIGATION OF SOLID SOLUTIONS IN THE SYSTEM LA4-XBAXNI3O10+Δ: UDC 546.42'654'74 (Bulletin of the Taras Shevchenko National University of Kyiv. Chemistry, 2016)
Oxide samples with chemical composition La4-xBaxNi3O10+δ, where 0≤x≤2, related to Ruddlesden-Popper phases were synthesized by coprecipitation method of components from nitrates solutions by 0.25 M K2CO3 solution with following calcination of obtained blend by 950оС during 100 hours. X-ray phase analysis of the obtained samples show that the substitution of lanthanum on barium with 0
Keywords: ruddlesden popper phases, oxygen nonstoichiometry, electrical properties